2011
DOI: 10.2503/hrj.10.367
|View full text |Cite
|
Sign up to set email alerts
|

Super-high Density Planting of Fig (Ficus carica L.) for Early Recovery from Sick Soil and Low Temperature Injury

Abstract: We investigated the effect of super-high density planting for early recovery from sick soil and low temperature injury in fig (Ficus carica L. 'Masui Dauphine') over a five-year period. Towards this end, fig trees were planted at either 0.8 or 2.0 m planting distance (super-density planting), in comparison to the conventional 4.0 m planting distance on the continuous cropping field. It was observed that super-high density planting with 0.8 m was superior to 2.0 and 4.0 m planting distances for maintaining tree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 3 publications
2
9
0
Order By: Relevance
“…The internodes of shoots tended to be longer for novel trained trees and were significantly longer than controls in the trees with 0.6 m spacing. The shoot diameters tend to be larger with narrower tree spacing; this can be explained by enhanced shoot vigor with dense planting (Mano et al, 2011). The basal diameters of novel training shoots were significantly larger than in controls with 0.6 m and 6.6 m tree spacing.…”
Section: Resultsmentioning
confidence: 89%
“…The internodes of shoots tended to be longer for novel trained trees and were significantly longer than controls in the trees with 0.6 m spacing. The shoot diameters tend to be larger with narrower tree spacing; this can be explained by enhanced shoot vigor with dense planting (Mano et al, 2011). The basal diameters of novel training shoots were significantly larger than in controls with 0.6 m and 6.6 m tree spacing.…”
Section: Resultsmentioning
confidence: 89%
“…The mean tree height, canopy spread and trunk circumference over the five year period were generally higher under higher tree densities of 1000 and 800 trees per hectare than lower tree densities, more so in the vigorous Poona cultivar than the less vigorous Deanna, as evident from tables 1 and 2. Mano et al, (2011) observed that, planting with 0.8 m distance within trees and 3.5 m in between rows was superior for maintaining tree vigor and yields under continuous cropping conditions as well as for early recovery from sick soil as compared to 2.0 and 4.0 m planting distances respectively in fig cultivar 'Masui Dauphine'. Kumar et al, (2014) also noted maximum leaf production, shoot growth, tree height and tree circumference under closer spacing in Deanna fig.…”
Section: Vegetative Growthmentioning
confidence: 95%
“…Similarly, other studies in fig (Kumar et al, 2014;Mano and Hamada, 2005;Hosomi et al, 2013) concluded that fruit quality parameters (TSS and titratable acidity) were unaffected by planting distances. However, Mano et al, (2011) noted significant differences in fruit quality parameters under closer planting distances in fig. They reported lower TSS, TA and antioxidants contents at 0.8m planting distance compared to 2 and 4m.…”
Section: Fruit Qualitymentioning
confidence: 97%
See 2 more Smart Citations